2013
DOI: 10.1371/journal.pone.0078099
|View full text |Cite
|
Sign up to set email alerts
|

IL-33, but Not IL-25, Is Crucial for the Development of House Dust Mite Antigen-Induced Allergic Rhinitis

Abstract: Both interleukin (IL)-33 and IL-25 induce Th2 cytokine production by various cell types, suggesting that they contribute to development of allergic disorders. However, the precise roles of IL-33 and IL-25 in house dust mite (HDM)-induced allergic rhinitis (AR) remain unclear. Both IL-33 and IL-25 were produced mainly by nasal epithelial cells during HDM-induced AR. Eosinophil and goblet cell counts in the nose and IL-5 levels in lymph node cell culture supernatants were significantly decreased in IL-33-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 31 publications
3
44
1
1
Order By: Relevance
“…Although epithelial barrier tissues and endothelial cells are generally known to express IL-33 (36,37), some immune cells, such as macrophages and dendritic cells, can produce IL-33 under certain inflammatory conditions (38,39). However, the level of IL-33 produced by hematopoietic cells is much less than that from epithelial cells (39,40), and tissuederived IL-33 is critical for induction of allergic inflammation (41). IL-33 signals through the ST2/IL-1RAcP complex, mainly expressed in ILC2, mast cells, basophils, eosinophils, Th2 cells, NKT, and NK cells (25,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Although epithelial barrier tissues and endothelial cells are generally known to express IL-33 (36,37), some immune cells, such as macrophages and dendritic cells, can produce IL-33 under certain inflammatory conditions (38,39). However, the level of IL-33 produced by hematopoietic cells is much less than that from epithelial cells (39,40), and tissuederived IL-33 is critical for induction of allergic inflammation (41). IL-33 signals through the ST2/IL-1RAcP complex, mainly expressed in ILC2, mast cells, basophils, eosinophils, Th2 cells, NKT, and NK cells (25,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 plays a role in other models of allergic disease, including allergic rhinitis and chronic rhinosinusitus through activation of ILC2s, basophils and mast cells (Haenuki et al, 2012; Kato, 2015; Mjösberg et al, 2011; Nakanishi et al, 2013). In humans, chronic eosinophilic rhinosinusitis with nasal polyps is associated with increased epithelial IL-33 and IL-13 + ILC2s (Shaw et al, 2013).…”
Section: Il-33 In Type 2 Immune Responsesmentioning
confidence: 99%
“…However, the functional importance of immune cell‐derived IL‐33 in allergic immune responses is not fully understood. Indeed, a recent study showed that IL‐33 produced by tissue cells, but not that produced by immune cells, was essential for allergen‐driven airway inflammation …”
Section: Expression Of Il‐33mentioning
confidence: 99%